Imagined otherness fuels blatant dehumanization of outgroups - Austin van Loon; Amir Goldberg; Sameer B. Srivastava (Communications Psychology)
Abstract Dehumanization of others has been attributed to institutional processes that spread dehumanizing norms and narratives, as well as to individuals’ denial of mind to others. We propose that blatant dehumanization also arises when people actively contemplate others’ minds. We introduce the construct of imagined otherness—perceiving that a prototypical member of a social group construes an important facet of the social world in ways that diverge from the way most humans understand it—and argue that such attributions catalyze blatant dehumanization beyond the effects of general perceived difference and group identification. Measuring perceived schematic difference relative to the concept of America, we examine how this measure relates to the tendency of U.S. Republicans and Democrats to blatantly dehumanize members of the other political party. We report the results of two pre-registered studies—one correlational (N = 771) and one experimental (N = 398)—that together lend support for our theory. We discuss implications of these findings for research on social boundaries, political polarization, and the measurement of meaning.